Residents’ Perception of Educational Tourism in Jakarta, Indonesia - HENDIJANI, Roozbeh Babolian (Journal of Environmental Management and Tourism, 2016)
Residents’ perception of tourism development has received increasing interest from tourism industry managers. Although the number of tourists visiting Indonesia is increasing, the fact about educational tourism and its effect on residents’ perception has not been explored. The objective of this study is to understand the implication of educational tourism in relation to local residents. A qualitative approach was conducted with some local residents. The study revealed those local residents’ both negative and positive aspects of educational tourism. In practice, this research will have benefit for the Indonesian government, the host university and for the local residents in the area.
Keywords: educational tourism; resident perception; international students; Indonesia; qualitative